Implications of Ocean Acidification for Marine Microorganisms from the Free-Living to the Host-Associated - O'Brien, Paul A.; Morrow, Kathleen M.; Willis, Bette L.; Bourne, David G. (Frontiers in Marine Science, 2016)
Anthropogenic CO2 emissions are causing oceans to become more acidic, with consequences for all marine life including microorganisms. Studies reveal that from the microbes that occupy the open ocean to those intimately associated with their invertebrate hosts, changing ocean chemistry will alter the critical functions of these important organisms. Our current understanding indicates that bacterial communities associated with their host will shift as pH drops by another 0.2-0.4 units over the next 100 years. It is unclear what impacts this will have for host health, however increased vulnerability to disease seems likely for those associated with reef corals. Natural CO2 seeps have provided a unique setting for the study of microbial communities under OA in situ, where shifts in the bacterial communities associated with corals at the seep are correlated with a decline in abundance of the associated coral species. Changes to global biogeochemical cycles also appear likely as photosynthesis and nitrogen fixation by pelagic microbes becomes enhanced under low pH conditions. However, recent long-term studies have shown that pelagic microbes are also capable of evolutionary adaptation, with some physiological responses to a decline in pH restored after hundreds of generations at high pCO2 levels. The impacts of ocean acidification (OA) also will not work in isolation, thus synergistic interactions with other potential stressors, such as rising seawater temperatures, will likely exacerbate the microbial response to OA. This review discusses our existing understanding of the impacts of OA on both pelagic and host-associated marine microbial communities, whilst highlighting the importance of controlled laboratory studies and in situ experiments, to fill the current gaps in our knowledge.